2017
DOI: 10.1016/j.sleep.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic biomarkers in community obese children: effect of obstructive sleep apnea and its treatment

Abstract: Concurrent obesity and OSAS could promote metabolic and inflammatory alterations, and the latter appeared to be sensitive to OSAS treatment outcomes. ClinicalTrials.gov Identifier: NCT01322763.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 47 publications
1
14
0
3
Order By: Relevance
“…Out of the 62 subjects with OSA, 10 were started on CPAP corresponding to an incidence of 16%. Indication for CPAP was defined as moderate-to-severe OSA defined as ASI > 10 without endoscopic evidence of adenotonsillar hypertrophy ( 37 ).…”
Section: Cpap In Obese Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of the 62 subjects with OSA, 10 were started on CPAP corresponding to an incidence of 16%. Indication for CPAP was defined as moderate-to-severe OSA defined as ASI > 10 without endoscopic evidence of adenotonsillar hypertrophy ( 37 ).…”
Section: Cpap In Obese Childrenmentioning
confidence: 99%
“…This last finding is intriguing and clinically relevant suggesting increased energy expenditure during sleep ( 32 ). Alonso-Alvarez et al ( 37 ) studied the effects of different OSA treatments on several markers of the metabolic syndrome. Only a limited number of patients on CPAP were included.…”
Section: Cpap In Obese Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7] In adults, it has been clearly demonstrated that OSA, the associated intermittent nocturnal hypoxemia and other sleep disturbances, has deleterious clinical consequences contributing to obesity, metabolic syndrome and cardiovascular and renal diseases [8][9][10][11][12] with some of this evidence previously synthesised. [13][14][15][16] In children, emerging data over the past few years also suggest these associations although available studies have revealed conflicting results [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and evidence synthesis is less available.…”
Section: Introductionmentioning
confidence: 99%
“… 18 36 37 Evidence showing the implications of treating obesity to ameliorate OSA has started to emerge. 38 39 As well, the effect of treating OSA on obesity management has also been explored by more recent studies, 30 40–43 justifying the need of a systematic review.…”
Section: Introductionmentioning
confidence: 99%